2011
DOI: 10.1152/jn.00247.2010
|View full text |Cite
|
Sign up to set email alerts
|

Reorganization of Finger Coordination Patterns During Adaptation to Rotation and Scaling of a Newly Learned Sensorimotor Transformation

Abstract: Liu X, Mosier KM, Mussa-Ivaldi FA, Casadio M, Scheidt RA. Reorganization of finger coordination patterns during adaptation to rotation and scaling of a newly learned sensorimotor transformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 78 publications
4
47
0
Order By: Relevance
“…Here, by using a task that had considerable motor redundancy, we showed that learning a prior task not only influenced performance of the second task, but also that the movement solutions used to solve the second task were contingent upon those learned in first task (as indicated by the null space dispersion). The results support the hypothesis that learning rarely occurs on a blank slate (Zanone and Kelso, 1992;Kelso, 1995) and that learning can be influenced by previously learned (or intrinsic) patterns of coordination (Ranganathan and Newell, 2009;Ganesh et al, 2010;Liu et al, 2011;de Rugy et al, 2012), and may include even compensatory coordination patterns such as those seen after stroke (Raghavan et al, 2010). These results further suggest that models of motor learning and skill transfer need to account for the influence of existing repertoire of coordination patterns in addition to more common considerations of optimality (e.g., the minimization of effort or kinematic errors).…”
Section: Influence Of Prior Learned Coordination Patterns On Motor Lesupporting
confidence: 78%
See 3 more Smart Citations
“…Here, by using a task that had considerable motor redundancy, we showed that learning a prior task not only influenced performance of the second task, but also that the movement solutions used to solve the second task were contingent upon those learned in first task (as indicated by the null space dispersion). The results support the hypothesis that learning rarely occurs on a blank slate (Zanone and Kelso, 1992;Kelso, 1995) and that learning can be influenced by previously learned (or intrinsic) patterns of coordination (Ranganathan and Newell, 2009;Ganesh et al, 2010;Liu et al, 2011;de Rugy et al, 2012), and may include even compensatory coordination patterns such as those seen after stroke (Raghavan et al, 2010). These results further suggest that models of motor learning and skill transfer need to account for the influence of existing repertoire of coordination patterns in addition to more common considerations of optimality (e.g., the minimization of effort or kinematic errors).…”
Section: Influence Of Prior Learned Coordination Patterns On Motor Lesupporting
confidence: 78%
“…1) having 2 rows and 20 columns (cf. Mosier et al, 2005;Liu and Scheidt, 2008): Figure 1. Experimental setup.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus global generalization for visuomotor gain can also be explained by our simplicity/familiarity hypothesis. As extreme cases of unfamiliar perturbations, a recent study examined the learning of an arbitrary mapping from multi-finger movements to a cursor movement, a completely novel task where prior experience was minimally applicable (Liu et al 2011). Not surprisingly, generalization across directions was found to be very narrow.…”
Section: Discussionmentioning
confidence: 99%